Application of a wireless apnea monitoring device for crisis alertness and sleep diagnosis - Ademola Abdulkareem; Tobiloba Emmanuel Somefun; Victoria Oguntosin; Princess Oahimire (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Over the past five decades, obstructive sleep apnea has been noted as a prevalent symptom in adults with escalated health conditions like stroke, obesity, high blood pressure, cardiovascular complications and chronic kidney diseases; to mention but a few. Apnea hypopnea index (AHI) is the average number of apnea or hypopnea events which occur during a complete sleep cycle per hour. It is a measure of determining the severity of sleep apnea, where an index range of 5 to 15 indicates mild, 15 to 30, moderate and above 30 denotes severe sleep apnea. In a bid to perform this diagnosis, several approaches have been considered. In this study vibrating sensor module and an Arduino Uno Rev3 microcontroller which retrieve breathing status data during sleep and identifies apnea events is proposed. The developed monitoring device displays the apnea count, effectively, which can be used to determine AHI. It also incorporates a Bluetooth module for wireless, real-time data monitoring which allows for more comfortable usability. The result is the successful implementation of an efficient, cost-effective system which can be used for sleep apnea diagnosis and provides preventive health care measures.